Drug Trafficking and Violence in Central America and Beyond - Demombynes, Gabriel (World Bank, Washington, DC, 2017)
This paper examines the relationship between narcotics trafficking and violence in Central America. The first part of the paper addresses particular questions posed for the 2011 World Development Report and examines several competing hypothesis on the drivers of crime in Central America. A key finding is that areas exposed to intense narcotics trafficking in Central America suffer from higher homicide rates. Drug trafficking has corrupted state institutions, which have been overwhelmed by the resources deployed by trafficking organizations. The second part of the paper reviews the reasons drug trafficking and anti trafficking enforcement are associated with violence in general and consider policy options.